The Effects of Legal and Extralegal Factors on Probation Revocation Decisions - Verrecchia, P.J.; Ling, Eric (International Journal of Criminology and Sociology, 2013)
Abstract: This study attempts to further the understanding of how legal and extra legal factors affect the decision of criminal justice professionals, specifically, adult probation officers. The findings show that while both legal and extra legal factors were significant in the decision to revoke probation and the length of the sentence, the factors were different for each decision.